Pavement drainage : theory and practice - Sivakumar Babu, G. L.; Kandhal, Prithvi S.; Kottayi, Nivedya Mandankara; Mallick, Rajib Basu; Veeraragavan, A. (CRC Press, 2020)
This book provides complete coverage of surface and subsurface drainage of all types of pavements for highways, urban roads, parking lots, airports, and container terminals. It provides up-to-date information on the principles and technologies for designing and building drainage systems and examines numerous issues, including maintenance and designing for flood events. Practical considerations and sophisticated analysis, such the use of the finite element method and unsaturated soil mechanics, anisotropy and uncertainties, are presented. This book allows civil engineers to make the best use of their resources to provide cost effective and sustainable pavements. Features Presents a holistic consideration of drainage with respect to pavement performance. Includes numerous practical case studies. Examines flooding and the impacts of climate change. Includes PowerPoint slides which include quizzes, schematics, figures, and tables